2019
DOI: 10.1016/j.aninu.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Coarse corn particles cause a negative effect on eggshell quality of semi-heavy laying hens

Abstract: One of the possible ways to optimize the productive performance of poultry is through the physical processing of ingredients, which can improve the use of nutrients in these animals. In this context, this study was to evaluate the effects of different corn particle sizes in diets on the productive performance and egg quality of semi-heavy laying hens. Sixty naked neck laying hens were used from 24 weeks of age and distributed in a completely randomized design. Experimental diets in different treatments contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In the present study, the responses to grinding sieve size depended mainly on the interaction with drying temperature and not on the grinding sieve size itself. Although to our knowledge, there is limited data on the effects of grinding sieve size on yolk carotenoid content, Oliveira et al (2019) reported that hens fed fine and medium corn particles had higher yolk pigmentation than hens fed coarse particles. This is consistent with the results of the present study and suggests that the yolk content and deposition efficiency of some carotenoids, such as zeaxanthin ( Table 5A ), may increase in laying hens with the reduction in the grain particle size.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, the responses to grinding sieve size depended mainly on the interaction with drying temperature and not on the grinding sieve size itself. Although to our knowledge, there is limited data on the effects of grinding sieve size on yolk carotenoid content, Oliveira et al (2019) reported that hens fed fine and medium corn particles had higher yolk pigmentation than hens fed coarse particles. This is consistent with the results of the present study and suggests that the yolk content and deposition efficiency of some carotenoids, such as zeaxanthin ( Table 5A ), may increase in laying hens with the reduction in the grain particle size.…”
Section: Discussionmentioning
confidence: 98%
“…Pulverization treatment of P. carotinifaciens powder increased the efficiency of carotenoid deposition in egg yolks ( Honda et al., 2020b ). Moreover, the smaller size of corn particles can increase surface contact with intestinal enzymes and carriers, favoring the enterohepatic absorption of carotenoids for the pigmentation of egg yolks, thereby allowing more effective absorption of carotenoids ( Oliveira et al., 2019 ). In addition, the saponification of natural paprika and marigold pigmentation products resulted in increased pigmentation quality of these products.…”
Section: Enrichment Efficiency Of Carotenoidsmentioning
confidence: 99%